Chapter 3
The logic circuit shown in the diagram directly implements which of the Boolean expressions given below?
((x + y')y + (x + y'))'
The logic circuit shown in the diagram directly implements which of the Boolean expressions given below?
((x + y)z)' + xy'
The logic circuit shown in the diagram directly implements which of the Boolean expressions given below?
((xy)'(x + y'))'
The logic circuit shown in the diagram directly implements which of the Boolean expressions given below?
(xy + z')(y + z)'
The Boolean function F(x, y) = x'y' + x'y + xy is equivalent to:
(xy')'
The Boolean function F(x, y) = x'y' + x'y + xy' is equivalent to:
(xy)'
The truth table shown below is supposed to reflect the function F(x, y, z) = (x'y'+ yz) + (xy' + yz') but two lines are in error. Identify them.
1 and 2
The truth table shown below is supposed to reflect the function F(x, y, z) = y(x + z') but two lines are in error. Identify them
3 and 4
The Boolean expressions x(x + y) = x and x + xy = x are examples of (the):
Absorption Law
The Boolean AND operation is also known as:
Boolean product
The Boolean OR operation is also known as:
Boolean sum
The Boolean expressions (xy)' = x' + y' and (x + y)' = x'y' are examples of (the):
DeMorgan's Law
The Boolean expressions, x + (yz) = (x + y)(x + z) and x(y + z) = x y + xz, are examples of (the):
Distributive Law
The Boolean expressions, xx = x and x + x = x, are examples of (the):
Idempotent Law
The Boolean function F(x, y) = x'y + xy' + (x'+y')(xy) can be simplified to:
x y
Which of the following equations correctly reflects the truth table shown below?
x'y'z + x'yz' + xy'z + xyz
Which of the following equations correctly reflects the truth table shown below?
x'yz' + x'yz + xy'z' + xyz' + xyz
The Boolean function F(x, y, z) = y(x'z + xz) + x'yz' + xy'z simplifies to:
xz + x'y
The Boolean function F(x, y) = x'y' + xy' + y(xy') can be simplified to:
y'
The logic circuit shown in the diagram directly implements which of the Boolean expressions given below?
y(x' + z) + (xz + y)
The Boolean function F(x, y, z) = (y + x)(y + x')(y'+ z) is equivalent to:
yz
The Boolean function F(x, y, z) = y'z + x'yz + xyz is equivalent to:
z